An analysis of the mediating effect of presenteeism between job crafting and organizational silencing in junior nurses: a cross sectional study - Yang, Na; Wang, Dandan; Wei, Chen; Wang, Jingwen; Yuan, Liping (Frontiers in Psychology, 2025)
BackgroundOrganizational silence is prevalent in the healthcare industry, especially among junior nurses likelier to remain silent on work issues due to their lack of experience and weak voice. This negative behavior not only affects the efficiency of team communication but may also reduce the quality of care. At the same time, presenteeism (working with illness or inefficiency) is becoming increasingly prominent in the nurse population, further exacerbating burnout and organizational silence. Although research suggests that job crafting improves employee initiative, how it inhibits organizational silence by reducing presenteeism is unclear. Therefore, it is important to explore the relationship between the three to optimize nursing management strategies and enhance nurses’ occupational health.ObjectiveTo explore the mediating effect of presenteeism between organizational silencing and job crafting in junior nurses, to provide intervention targets for clinical nursing management, to reduce organizational silencing, and to optimize nurses’ occupational behavior.MethodsThis study adopted a cross-sectional survey design and strictly followed the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines to ensure transparency in research methods and completeness in reporting. A convenience sample of 170 junior nurses (with ≤5 years of clinical experience) was selected from a tertiary hospital in Wuhu City, Anhui Province, and data were collected using a structured questionnaire, and questionnaires were administered using the General Information Questionnaire, Stanford Presenteeism Scales (SPS-6), Job Crafting Questionnaire (JCQ), and Nurse organizational silence assessment questionnaire (NOSAQ). Relationships between variables were clarified by Pearson correlation analysis and the mediating effect of presenteeism was tested by Bootstrap method.ResultsThe total score of presenteeism was (15.71 ± 5.65), which was moderately high; the total score of Job crafting (69.35 ± 12.28) showed that the nurses‘ability to proactively restructure their work needed to be improved; and the total score of organizational silence (57.27 ± 14.25) showed that the nurses’ tendency to negatively avoid organizational issues was more obvious. Correlation analysis showed that Job crafting was significantly negatively correlated with organizational silence (r = −0.671, p < 0.01) and presenteeism (r = −0.708, p < 0.01); organizational silence was significantly positively correlated with presenteeism (r = 0.743, p < 0.01). Mediation effect analyses indicated that presenteeism partially mediated the relationship between job crafting and organizational silence, with a mediation effect value of 47% of the total effect.ConclusionPresenteeism is a significant mediating pathway for junior nurses’ Job crafting to influence organizational silence. Nursing managers can improve the status quo by intervening in two pathways: on the one hand, directly improving nurses’ job reinvention ability (e.g., empowering participation in decision-making, optimizing task design), and on the other hand, reducing presenteeism (e.g., improving the sick leave system, reducing work pressure), which can effectively reduce the incidence of organizational silencing, and promote team communication and organizational effectiveness. The findings provide a theoretical basis and practical direction for the development of targeted management strategies.